Numerical analysis in rock engineering 2 - Poon, Hong Wai. (2011)
Forays into underground development are an increasingly popular means of overcoming land shortage in Singapore. Although rock dominates the geology of northern, western and central Singapore, the mechanics of underground structures in these rock formations, particularly in their interactions with discontinuities, have yet to be studied extensively. Acquiring such knowledge may help engineers design underground caverns of higher safety and service life.The report makes a distinction between rock and soil as well as rock mechanics and rock mass mechanics. Rock mass mechanics accounts for the effect of discontinuities and is the basis of scoring in the Rock Mass Rating system, whose scores provide initial design guidance without aid of computers. Modern modelling methods are also discussed, of which discontinuous deformation analysis (DDA) stands out for its ability to realistically depict rock mass geometry and discontinuity parameters.